2018
DOI: 10.21010/ajid.v12i1s.2
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping of Human Pappilomavirus in Cervical Precancerous Lesion and Squamous Cell Carcinoma at Dr. Soetomo Hospital, Surabaya, Indonesia

Abstract: Background: Cervical cancer caused by human papilloma virus (HPV), is the second most common cancer for women. This cancer is distributed worldwide, with ~80% of cases are found in the developing countries. In Indonesia, data of HPV genotypes are still limited and do not represent all regions of the country. Thus, here we report genotyping of HPV samples collected from the Dr. Soetomo Hospital Surabaya Indonesia patients, in 2013. Materials and Method: A cross sectional study was performed using 68 paraffin bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 8 publications
1
10
1
1
Order By: Relevance
“…We found that 59% of the HPV-positive samples had multiple HR-HPV infections. Other studies reported multiple HPV infections: 68.2% in HSIL [35] and 13.2% in FFPE samples [36]. Another study reported that 38.2% of the cases had a multiple HPV infections, which is lower than the value reported in our study (59%).…”
Section: Discussioncontrasting
confidence: 93%
“…We found that 59% of the HPV-positive samples had multiple HR-HPV infections. Other studies reported multiple HPV infections: 68.2% in HSIL [35] and 13.2% in FFPE samples [36]. Another study reported that 38.2% of the cases had a multiple HPV infections, which is lower than the value reported in our study (59%).…”
Section: Discussioncontrasting
confidence: 93%
“…► The introduction of the HPV bivalent vaccine as part of the national vaccination program is recommended. The inconclusive results of a single genotype were further analyzed with AMPLIQUALITY HPV-TYPE EXPRESS (version 3.0, AB ANALITICA, Italy) according to the manufacturer's instructions (18). This kit can identify 40 HPV individual genotypes based on the amplification of a 145-bp fragment in the L1 region of the HPV genome, followed by a reverse line blot assay.…”
Section: Hpv Detection Through Conventional Polymerase Chain Reactionmentioning
confidence: 99%
“…24 The common HR-HPV in men with condyloma acuminata was HPV 16 and followed by HPV 18.25 Our previous study showed that the most common HPV infected in men with condyloma acuminata was LR-HPV were HPV 6, HPV 11 and HR-HPV were HPV 18, 51, 52, 82 26 and in cervical precancerous lesion and squamous cell carcinoma were is HPV 16 (62.68%), then followed by HPV 18 (20.9%), HPV 45 (5.97%), 52 (5.97%), and 67 (4.48%). 27 However, condyloma acuminata is usually caused by LR-HPV infection, this finding demonstrated that LR-HPV co-infection with HR-HPV. HR-HPV such as HPV 16, HPV 18, HPV 45, HPV 52, and 67 was HPV have been founded in cervical cancer and precancerous lesion.…”
Section: Discussionmentioning
confidence: 88%
“…HR-HPV such as HPV 16, HPV 18, HPV 45, HPV 52, and 67 was HPV have been founded in cervical cancer and precancerous lesion. 27 Several other studies have also shown that HPV 16, as well as LR-HPV (HPV 6 and 11) were also found in penile intraepithelial neoplasia.8 HPV 16 and HPV 18 were founded on vulval and vaginal cancel cell.28 Persistent infection of HR-HPV is a risk factor for progression of cell transformation into malignant cells. The determination of genotype HPV, including HR-HPV can be used to predict the malignant transformation of condyloma acuminata into invasive cancer in the anogenital area and also to establish a preventive program by vaccination.…”
Section: Discussionmentioning
confidence: 98%